Potential role of geranylgeraniol in managing statin-associated muscle symptoms: a COVID-19 related perspective - Tan, Barrie; Chin, Kok-Yong (Frontiers in Physiology, 2023)
Myopathy is the most common side effect of statins, but it has not been addressed effectively. In anticipation of its wider use as a small molecule to complement the current Covid-19 management, a pharmacological solution to statin-associated muscle symptoms (SAMS) is warranted. Statins act by suppressing the mevalonate pathway, which in turn affects the downstream synthesis of isoprenoids required for normal physiological functions. CoQ10 and geranylgeraniol (GG) syntheses are reduced by statin use. However, CoQ10 supplementation has not been shown to reverse SAMS. GG is an obligatory substrate for CoQ10 synthesis, an endogenous nutrient critical for skeletal muscle protein synthesis. Multiple studies showed GG supplementation is effective in reversing SAMS. This opinion paper proposes employing GG to prevent SAMS in pleiotropic statin use, including usage in the post-Covid-19 pandemic era.